Promotion & marketing for broadcasting, cable & the web, fourth edition (Focal Press, 2002)
Promotion & Marketing for Broadcasting, Cable and the Web has remained one of the only books about promotion for radio, TV, cable, and now the web. The latest edition of this highly-regarded textbook has been updated to encompass the enormous structural and economic changes in the industry since the early 90s. New emphasis is placed on the role of the World Wide Web and global marketing. The fourth edition brings the ever-evolving mission of the web into even greater focus with a new chapter on internet commerce and competition, and the widespread use if the internet as an advertising medium.